IDENTIFICATION OF MISCONCEPTIONS IN PHYSICS LEARNING - Cindi Alvionita Lestari; Rugaya (Journal of Learning and Technology in Physics, 2024)
occur in class X SMA students in Medan City regarding parabolic motion. This type of research is included in descriptive research. Based on the regional sample used in this research, the schools selected were located in the city center, mid-city and suburbs, namely SMAN 18, SMAN 7 and SMAN 11 Medan respectively. The number of samples taken by each school was SMAN 18 with 36 students, SMAN 7 with 36 students, and SMAN 11 with 36 students. The research instrument is in the form of reasoned multiple choice questions totaling 15 questions. Before these test questions are used, the instrument is first validated by experts. After the tests were carried out in three schools, the data was analyzed using the CRI (Certainty of Response Index) method. The research results obtained showed that the misconceptions experienced at SMAN 18 Medan were 52.59%, at SMAN 7 Medan it was 60.37% and at SMAN 11 Medan it was 41.11%. It was concluded that misconceptions among class. Keywords: Misconceptions, parabolic motion, concept understanding